MUSIK SEBAGAI MEDIA PEMBELAJARAN IPSKELAS V SD MUHAMMADIYAH KALAKIJO - dan listiana Windiyawati, Abiy Rimabethe, Isdiyono (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
Social sciences are the field of disciplines exploring phenomenon, fact and draft insocial issues. However, many students have problems in understanding them. One of theproblems is because the teaching method is mainly concerned with memorizing. SDMuhammadiyah Kalakijo is one of the schools having this problem. The students’ scoreswere under the minimum mastery criteria. Music is considered as media that can beused to solve this problem.This classroom action research employed Kemmis and Taggart’s Model anddescriptive-qualitative method. The process of this research was monitored using testand observation technique. The subject of this research was the students Grade V at SDMuhammadiyah Kalakijo.The result of the research shows that music can be used to increase the scores ofcognitive, affective, and psychomotor aspect. The score before the treatment was 41.8,7.31 in the first cycle and 77.2 in the second cycle. Meanwhile, affective and psychomotoraspect increase from 50% for high, 33% for medium and 17% for low to 73% for high, 18%for medium and 9% for low in the second cycle.Key words: music, learning media, social science, Grade V SD Muhammadiyah Kalakijo